Analisis Pengaruh Karakteristik Individu, Beban Kerja, Dan Komitment Organisasi Terhadap Kinerja Karyawan Dimediasi Kepuasan Kerja Pada Pt Industrial Multi Fan - Setyabudi, Lilik; Rusdianti, Endang; Santoso, Djoko (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research is to test and analyze the influence of Individual Characteristics, Workload, and Organizational Commitment on employee performance mediated by Job Satisfaction. Empirical study at PT Industrial Multi Fan. The problem faced by PT Industrial Multi Fan is a decrease in target achievement in 3 consecutive years. Using descriptive quantitative research methods, as well as the SmartPLS analysis method, 4 research was carried out. The population of this research is all employees of PT Industrial Multi Fan, totaling 84 employees. The sample is the same as the population.The results of the analysis show that Individual Characteristics, Workload and Organizational Commitment have a significant effect on employee performance. Job satisfaction is able to mediate the influence of individual characteristics, workload and organizational commitment on employee performance. Based on the Adjusted R Square value, it explains that individual characteristics, workload and organizational commitment influence employee performance by 62.8%.